2022
DOI: 10.3390/agronomy13010011
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Nitrogen Application and Irrigation on Water Use, Growth and Tuber Yield of Potato under Subsurface Drip Irrigation

Abstract: Potatoes are a high-value crop with a shallow root system and high fertilizer requirements. The primary emphasis in potato production is minimizing nitrogen-leaching losses from the shallow root zone through fertigation. Therefore, a field experiment was conducted for two consecutive years, 2018–2019 2019–2020 to assess the effect of nitrogen and irrigation amount and frequency on tuber yield, water balance components and water productivity of potatoes under surface and subsurface drip irrigation. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Deep percolation was accepted zero when soil moisture was less than field capacity. When soil moisture after irrigation or precipitation surpassed field capacity, deep percolation was evaluated as the difference between field capacity and soil moisture plus irrigation/precipitation 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Deep percolation was accepted zero when soil moisture was less than field capacity. When soil moisture after irrigation or precipitation surpassed field capacity, deep percolation was evaluated as the difference between field capacity and soil moisture plus irrigation/precipitation 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Increasing irrigation during the growth period rapidly increased the soil moisture, and appropriate soil moisture environment would accelerate crop water metabolism, open leaf stomata through signal transmission, increase crop transpiration, and increase water consumption [52]. Kaur et al [53] revealed that crop ET first rose and then declined with increasing fertilizer application, obtaining the largest value at 150 kg ha −1 nitrogen application. Our study reached similar conclusions.…”
Section: Wp and Nuementioning
confidence: 99%
“…This in turn helps in optimizing crop yields with higher drought tolerance [82]. In several studies, soil nitrogen (N) level was positively related to water use efficiency [83][84][85]. Potato cultivation is quite demanding in inorganic nutrients and adequate fertilization is a key factor for maximizing yield and producing tubers of high quality [86].…”
Section: Role Of Microbial Bioinoculants In Mitigating Postharvest Ch...mentioning
confidence: 99%